2009
DOI: 10.1016/s1130-6343(09)70996-1
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la prescripción al alta en urgencias. Impacto económico

Abstract: A prescription based on its active ingredients and a therapeutic and generic substitution produce a significant saving both for the patient and for the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…[12] In contrast to our study, the most common indication for drug prescription in the Indian study was infection (19%), while infection was the third most common indication for drug prescription in our study (15%). Paracetamol was also the most commonly prescribed drug (10%) in a study conducted at the ED in Spain,[11] which is similar to our study results, followed by ibuprofen-an NSAID-(9%) and omeprazole (7%). However, in the Spanish study,[11] the most common indication for drug prescribing was the GIT and metabolism (22%) followed by blood and hematopoietic system (2%), which is almost similar to our data.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[12] In contrast to our study, the most common indication for drug prescription in the Indian study was infection (19%), while infection was the third most common indication for drug prescription in our study (15%). Paracetamol was also the most commonly prescribed drug (10%) in a study conducted at the ED in Spain,[11] which is similar to our study results, followed by ibuprofen-an NSAID-(9%) and omeprazole (7%). However, in the Spanish study,[11] the most common indication for drug prescribing was the GIT and metabolism (22%) followed by blood and hematopoietic system (2%), which is almost similar to our data.…”
Section: Discussionsupporting
confidence: 90%
“…Paracetamol was also the most commonly prescribed drug (10%) in a study conducted at the ED in Spain,[11] which is similar to our study results, followed by ibuprofen-an NSAID-(9%) and omeprazole (7%). However, in the Spanish study,[11] the most common indication for drug prescribing was the GIT and metabolism (22%) followed by blood and hematopoietic system (2%), which is almost similar to our data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the percentages reported in the bibliography are similar [21,28] , they shouldn't be considered as optimal. There are generic drugs available for quite a considerable proportion of the drugs prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…GPS are not commonly used by hospital pharmacists. In Spain, the main problem for the extensive implementation of generic drugs is that traditionally they have not been used, mainly due to the limited information available to healthcare professionals and the absence of official lists of widely available generic medication [28] . It has been shown that the level of information held by physicians and the controversy about the therapeutic equivalence between generic medication and those of reference could be some of the crucial factors causing a lack of implementation of generic specialties.…”
Section: Discussionmentioning
confidence: 99%